Analisis Nilai-Nilai Karakter dalam Proses Pembelajarantematik Terpadu Di Kelas V SDN 05 Jaruai Bungus Teluk Kabung Kota Padang - Rossa, Rona; Delmata Ardilla, Yunny (LP2M Universitas Adzkia, 2023)
Education functions to develop abilities and shape the character and civilization of a dignified nation in order to make the nation's life more intelligent. The problem expressed in this research is what character values ​​are seen in the integrated thematic learning process in class V of elementary school. The aim of this research is to see the application of character values ​​in the integrated thematic learning process. The approach used in this study is a qualitative approach. The subjects of this research were fifth grade elementary school students. This research data was collected by conducting interviews, distributing questionnaires, documentation and observation. Data analysis in this research consists of four stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of this research were obtained from field research conducted at SDN 05 Jaruai Bungus Teluk Kabung, Padang City, academic year 2021/2022, namely that the dominant character values ​​seen in the integrated thematic learning process in class V at SDN 05 Jaruai Bungus Teluk Kabung, Padang City are character values. religious, honest, caring, responsible and disciplined. Based on research results from the results of the instruments that the author used during the integrated thematic learning process, there were religious character values ​​in 83% of the data, honest character values ​​in 78% of the data, disciplined character values ​​in 75% of the data, responsibility character values ​​in 90%. % data, and caring character values, there are 79% of students' data who apply character values ​​in class V of SDN 05 Jaruai Bungus Teluk Kabung, Padang City. Criteria for applying character values ​​at SDN 05 Jaruai Bungus Teluk Kabung, Padang City. Good character formed from now on will greatly determine the character of the nation in the future. Character will be well formed if that character is always implemented well in students' lives.